Development of small scale cell culture models for screening poloxamer 188 lot‐to‐lot variation. (19th August 2014) - Peng, Haofan; Hall, Kaitlyn M.; Clayton, Blake; Wiltberger, Kelly; Hu, Weiwei; Hughes, Erik; Kane, John; Ney, Rachel; Ryll, Thomas
<x xml:space="preserve">Abstract</x> Shear protectants such as poloxamer 188 play a critical role in protecting cells during cell culture bioprocessing. Lot‐to‐lot variation of poloxamer 188 was experienced during a routine technology transfer across sites of similar scale and equipment. Cell culture medium containing a specific poloxamer 188 lot resulted in an unusual drop in cell growth, viability, and titer during manufacturing runs. After switching poloxamer lots, culture performance returned to the expected level. In order to control the quality of poloxamer 188 and thus maintain better consistency in manufacturing, multiple small scale screening models were developed. Initially, a 5L bioreactor model was established to evaluate cell damage by high sparge rates with different poloxamer 188 lots. Subsequently, a more robust, simple, and efficient baffled shake flask model was developed. The baffled shake flask model can be performed in a high throughput manner to investigate the cell damage in a bubbling environment. The main cause of the poor performance was the loss of protection, rather than toxicity. It was also suggested that suspicious lots can be identified using different cell line and media. The screening methods provide easy, yet remarkable models for understanding and controlling cell damage due to raw material lot variation as well as studying the interaction between poloxamer 188 and cells. © 2014 American Institute of Chemical Engineers Biotechnol. Prog., 30:1411–1418, 2014